2011
DOI: 10.1109/tasc.2010.2083615
|View full text |Cite
|
Sign up to set email alerts
|

Quench Characteristics of a Cu-Stabilized 2G HTS Conductor

Abstract: Abstract-The prospect of medium/high field superconducting magnets using 2G HTS tapes is approaching to reality with continued enhancement in the performance of these conductors. Direct measurements of 1d adiabatic quench initiation and propagation of a Cu-stabilized 2G conductor have been carried out with spatial-temporal recording of temperature and voltage following the deposition of various local heat pulses to the conductor at different temperatures between 40K and 64K carrying different transport current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…When the applied current is greater than I c , the resistance of the superconducting part is assumed to follow the power law: ρ(T)=E c (J/J c (T)) n(T)−1 /J c (T). The resistivity of the non-superconducting part is equal to the resistivity of the damaged YBCO tape, which is warmed to about 600 degrees to destroy its superconductivity [23]. The current sharing between two parts in every segment can be calculated using iteration algorithm [24].…”
Section: Resultsmentioning
confidence: 99%
“…When the applied current is greater than I c , the resistance of the superconducting part is assumed to follow the power law: ρ(T)=E c (J/J c (T)) n(T)−1 /J c (T). The resistivity of the non-superconducting part is equal to the resistivity of the damaged YBCO tape, which is warmed to about 600 degrees to destroy its superconductivity [23]. The current sharing between two parts in every segment can be calculated using iteration algorithm [24].…”
Section: Resultsmentioning
confidence: 99%
“…Some research has already shown a more complex current sharing and normal zone propagation is expected for Roebel cables than those found in traditional superconducting composites due to the non-continuous touch contacts among the Roebel strands [1]- [3], [5]- [8]. Therefore, the standard method of experimental quench studies on adiabatic short conductors [9]- [11] becomes impractical for Roebel cables with long current sharing length [2].…”
Section: Introductionmentioning
confidence: 99%
“…On top of the YBCO film, a metallic layer of several micrometer thickness is deposited as a thermal stabilizer. Now that a coated high-temperature superconductor tape with the desired current performance has been realized, we must improve our understanding of the thermal stability of the system in order to meet the performance requirements for various applications [2,3]. To this end, we must precisely simulate the two-dimensional transient heat conduction in a superconducting tape that can be employed safely under all possible conditions, including low temperature and high magnetic field.…”
Section: Introductionmentioning
confidence: 99%